2021
DOI: 10.1186/s13104-021-05703-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of micro RNA-29 family in non-diabetic adults of diabetic and non-diabetic parents

Abstract: Objective MicroRNAs are known to regulate 60% of genes at post translational level. MicroRNAs including Micro RNA-29 family play a vital role in cellular activities and have validate role in numerous metabolic disorders inclusive of diabetes mellitus and its complications. While micro RNA profile changes years before the occurrence of disease. This cross-sectional study was conducted in non-diabetic adults of diabetic and non-diabetic parents to explore the early changes in expression of micro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Pakistan has a high burden of DM as well as TB. Type 2 DM is 16.98 % prevalent [13] . Different studies have reported a high rate of TB and DM co-morbidity in Pakistan.…”
Section: Burden Of Tb-dm In Asian Countriesmentioning
confidence: 99%
“…Pakistan has a high burden of DM as well as TB. Type 2 DM is 16.98 % prevalent [13] . Different studies have reported a high rate of TB and DM co-morbidity in Pakistan.…”
Section: Burden Of Tb-dm In Asian Countriesmentioning
confidence: 99%